Velocity model of the Tien-SHan lithosphere based on data of the Bachu-Balhash geotraverse (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
To determine the most characteristic features of the structure of the earth’s crust and upper mantle in the seismically active regions of the Tien Shan, two-dimensional P-velocity model of two geotravers Bachu- Balhash crossing seismic zones of the Tien Shan were developed. When constructing a two-dimensional velocity model of the earth’s crust and upper mantle of the Tien Shan and adjacent territories, an algorithm and program for a gradient model of the lithosphere were used. The resulting profile seismic tomographic velocity models were analyzed by comparison with the model of a three-dimensional seismic tomographic model and other authors in structural seismology
Keywords: earthquake records, seismic waves, earth’s crust, mantle, algorithm, homogeneities of lithosphere